TINGKAT PENGETAHUAN DENGAN PERILAKU WARGA DALAM MENJALANKAN PROTOKOL KESEHATAN DI MASA NEW NORMAL PANDEMI CORONA - Yehuda Imanuel Widyakusuma putra; Novita Verayanti Manalu (Coping: Community of Publishing in Nursing, 2020)
COVID-19 has become a global health problem in 2020. Until now, there is no cure for this disease. The best way to prevent this disease is to break the chain of spread of Covid-19 through isolation. However, restrictions on community activities have made the people's economy decline. To prevent this from happening, people must begin to adapt to new life habits or what is called the 'new normal life'. With the enactment of the new normal, people must carry out activities outside the home while adhering to health protocols that have been regulated by the government. This study aims to identify the level of public knowledge about Covid-19, the behavior of residents in carrying out health protocols in the new normal period, and to find out whether there is a significant relationship between the two variables. This research was conducted using a quantitative descriptive method with a survey approach. The population is the people who live in SK 14/31 Batu Gantung Village, Nusaniwe, Ambon City with a sample size of 50 people. Data collection was carried out by distributing knowledge and behavior questionnaires. Data were analyzed using Spearman correlation analysis with SPSS software. It was found that the level of public knowledge about Covid-19 was in the high category (52%). And people's behavior is in the good category (78%). There is a significant relationship between knowledge and people's behavior about the Covid-19 health protocol with a p-value of 0.065.